Analysis of Business Feasibility Studies in Management Aspects Case Study Services: Duck Sinjai Cab Restaurant. Bangkalan - Siti Aisah Hidayatul Hasanah (Penerbit Hellow Pustaka, 2024)
In today's economy, every company, whether in the service sector or not, must outperform both old and new competitors. To achieve the company's goals and improve the quality of a company, various aspects must be considered for improvement through consideration. This also applies to business actors in the culinary industry, such as restaurants. Restaurant evaluation is essential to increase sales and meet projected results. The purpose of this study is to find out whether the Sinjay Duck Restaurant has fulfilled the management aspect and to find out what management aspects can be applied to the Sinjay Duck Restaurant to improve the quality of the restaurant in the eyes of the public. The research method used is library research, data collection by searching for sources and constructing from various sources such as books, journals, and existing researches. The result of this study is that consumer satisfaction with service is less than optimal in serving, because in its implementation it turns out that the Sinjay Cab.Bangkalan Duck Restaurant has not implemented the points described by the author, especially in Service Quality and Getting Convenience.